2022
DOI: 10.18632/aging.204362
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal myocardial enzymes in the prediction of mortality and hypertension in COVID-19 patients: a retrospective study

Abstract: This study aims to determine the differences in myocardial enzymes in COVID-19 patients with and without hypertension. A total of 130 patients with COVID-19 in Yunmeng County People's Hospital were analyzed. The clinical manifestations and laboratory indicators were collected and analyzed. We found that COVID-19 patients with hypertension had higher mortality rate, greater age, and higher rates of basic disease such as diabetes than patients without hypertension. The γ-glutamyl transpeptidase (GGT), blood urea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…But there were some studies reporting con icting results as well. A study found CK-MB and CK had no signi cant difference in the prediction effect of the mortality in COVID-19 (41). The disagreement of CK and CK-MB found in our study made it di cult to clarify whether patients in the control group had more severe cardiac damage than patients in the baricitinib group.…”
Section: Discussioncontrasting
confidence: 76%
“…But there were some studies reporting con icting results as well. A study found CK-MB and CK had no signi cant difference in the prediction effect of the mortality in COVID-19 (41). The disagreement of CK and CK-MB found in our study made it di cult to clarify whether patients in the control group had more severe cardiac damage than patients in the baricitinib group.…”
Section: Discussioncontrasting
confidence: 76%
“…They further suggested that hs-TnI and CK-MB levels could serve as important biomarkers for identifying COVID-19 patients with cardiac damage [44]. Sha et al found that the levels of CK and CK-MB were significantly higher in patients with severe COVID-19 disease compared to those with non-severe disease, and the levels of CK and CK-MB correlated positively with the severity of the disease [45]. The study by Shi et al found that patients with cardiac injury had higher levels of troponin I, myoglobin, and CK-MB than those without cardiac injury.…”
Section: Creatine Kinase-myocardial Bandmentioning
confidence: 99%